Analisis Determinan Inklusi Keuangan Syariah pada Generasi Milenial di Kota Salatiga - Widyastuti, Emy; Iqmahanis Afisa (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This research aims to determine the influence of sharia financial literacy, financial technology, gender, age, education and income on sharia financial inclusion in the millennial generation of Salatiga City. This type of research is quantitative research using primary data in the form of questionnaires. The sample selected was 100 millennial generation respondents from Salatiga City using purposive sampling. The data analysis technique uses multiple linear regression with research results showing that sharia financial literacy and financial technology have a positive and significant effect on sharia financial inclusion, gender has an insignificant negative effect on sharia financial inclusion, age has a significant negative effect on sharia financial inclusion, education and income positive and insignificant effect on sharia financial inclusion.